The impact of bed occupancy rate and patient dependency on nurse fatigue in intensive care units - Eka Haryanti; Mugi Hartoyo; Shobirun Shobirun; Fika Indah Prasetya; Yetti Syafridawita; Priyo Sasmito; Nisa Arifani (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Intensive Care Unit (ICU) nurses are frequently exposed to high workloads resulting from elevated Bed Occupancy Rates (BOR) and the intensive care needs of patients with total dependency. These conditions increase the risk of physical and mental fatigue, which may compromise the quality of nursing care and patient safety. Purpose: To examine the association between BOR and patient dependency level with nurse fatigue in the ICU. Method: A quantitative approach, specially focusing on analytical survey and cross-sectional method. The study took place from April 2024 in Kanjeng Raden Mas Tumenggung Wongsonegoro Regional Hospital, Semarang. The independent variable was bed occupancy rate and patient dependency; dependent variable is nurse fatigue. Using total sampling, 81 respondents were selected with a split group of 29 ICU nurses to collect patients’ dependency level test, who met specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using Kendall Tau correlation. Results: Statistical analysis confirmed a significant correlation between BOR and nurse fatigue (p = 0.043), as well as between patient dependency and nurse fatigue (p = 0.048). Conclusion: The BOR and patient dependency rate were both key factors influencing fatigue among ICU nurses. These findings underscore the critical need for workload regulation informed by operational indicators to protect nurses' well-being and to uphold the quality of care in intensive settings.